Mapping Collaborative Governance In Indonesia Climate Village Program: A Bibliometric Analysis (2022-2025) - Pamungkas, Wahyu Adi; Yuwanto (Dinasti Research, 2025)
Although collaborative governance has been increasingly embraced as a fundamental approach for addressing complex environmental challenges, its application within nationwide climate adaptation programs has not been widely investigated. This paper focuses on how collaborative governance is portrayed and developed in studies concerning Indonesia’s Climate Village Program (ProKlim) during the 2022–2025 period. Bibliographic information was gathered using Publish or Perish (PoP) from Google Scholar, and analyzed through VOSviewer 1.6.20 to uncover publication patterns, topic clusters, and conceptual relationships. Out of 988 records identified, 402 were selected based on inclusion criteria for detailed analysis. The thematic visualization revealed three major themes: (1) local-level climate adaptation, (2) collaboration among stakeholders and governance, and (3) institutional and policy-related frameworks. Together, these clusters indicated that collaborative governance operates as a conceptual bridge, linking grassroots adaptation actions to national-level climate strategies. However, limited references to concepts such as multi-level governance, institutional capacity, and evaluation highlighted that theoretical integration and performance-based evaluation remain underdeveloped. The results aligned with the frameworks of Ansell and Gash (2008) and Emerson et al. (2012), while underlining the significance of inclusive involvement, supportive leadership, and flexible institutional structures. Up to now, research on ProKlim in Indonesia has mostly been descriptive and focused on individual case studies. Therefore, future research is encouraged to adopt more comparative and quantitative approaches to better assess how collaborative governance influences tangible improvements in local climate resilience. This bibliometric review contributes to both theory and practice by outlining the intellectual landscape of ProKlim-related studies and offering insights into how a more structured, evidence-driven, and participatory model of climate governance can be promoted.